การวิเคราะห์ผลตอบแทนและสวัสดิการของแรงงานในอุตสาหกรรมโรงแรมไทย - อรนันท์ คำสี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This research aims to study the structures of earnings and welfare in Thailand’s hotel industry. The research also tests the factors that affect these structures for presenting the ways to improve the labors of Thai hotel industry. There are 2 parts of data the researcher receives and the first data is about what the factor that affects the salary. The questionnaire is applied for this research with 1,024 data sets. The data are obtained by asking people who work in 3 to 5 stars hotels in 4 main travelling provinces, including Bangkok, Chiang Mai, Phuket, and Pattaya. Plus, this part of data is analyzed by using t-test. Secondly, the research is also analyzed by using OLS (Multiple Regression) and Tobit model from R Studio program to know what the factor that affects the structure of earning is. The research is analyzed with two variables, including the independent variable and controlled variable. The independent variable consists of wage, gender, age, education, marital status, working experience, working hours, the training, and the language use. Plus, the controlled variable includes type of work, and type of hotel. Moreover, the research is analyzed by interviewing general managers of 5 chosen hotels in Muang district, Chiang Mai for presenting the ways to improve the structures of earnings and welfare in Thailand’s hotel industry. The results reveal that there are several factors that affect the salary. First of all, the executive has the most effect on the salary since the executive has high education and working experience. Hence, the executive tends to have better opportunity to get promotion which lead to high salary. Secondly, the education is significant for hotel workers since the position they will get; it is regarded on their education. Therefore, every people who are a part of hotel industry have to have education. Furthermore, the third factor is the age. Hotels have rule about raising the salary of their employees in each year. Most employees who start working at young age tend to have higher salary that others due to their age of working and better working experience. Lastly, the variables which have no effect on the salary are the training and language use. However, the manager-interviews reveal that although the training and language use are not affects the salary directly, but they are still important for improving their institution. Due to Bangkok is the capital and also has higher cost of living than other provinces, the salary of hotel workers tend to be higher, as well. The rate of the salary for hotel workers in Bangkok is highest among all. The difference of salary is regarded by different location of hotel, too. Besides that, the type of working position is also related to the salary in the same way. Conversely, the customer service is related to the salary in opposite way. To illustrate, the customer service position got lesser rate of salary than the vocation position. Hotel workers also get different welfares including, uniform, food for hotel worker, social security, and the training.